Climate shapes the spatiotemporal variation in color morph diversity and composition across the distribution range of Chrysomela lapponica leaf beetle - Kozlov Mikhail V; Oudendijk Zowi; Forsman Anders; Lanta Vojtěch; Barclay Maxwell VL; Gusarov Vladimir I; Gustafsson Bert; Huang Zheng-Zhong; Kruglova Oksana Y; Marusik Yuri M; Mikhailov Yuri E; Mutanen Marko; et al. (WILEY, 2022)
Color polymorphism offers rich opportunities for studying the eco-evolutionary mechanisms that drive the adaptations of local populations to heterogeneous and changing environments. We explored the color morph diversity and composition in a Chrysomela lapponica leaf beetle across its entire distribution range to test the hypothesis that environmental and climatic variables shape spatiotemporal variation in the phenotypic structure of a polymorphic species. We obtained information on 13 617 specimens of this beetle from museums, private collections, and websites. These specimens (collected from 1830-2020) originated from 959 localities spanning 33 degrees latitude, 178 degrees longitude, and 4200 m altitude. We classified the beetles into five color morphs and searched for environmental factors that could explain the variation in the level of polymorphism (quantified by the Shannon diversity index) and in the relative frequencies of individual color morphs. The highest level of polymorphism was found at high latitudes and altitudes. The color morphs differed in their climatic requirements; composition of colour morphs was independent of the geographic distance that separated populations but changed with collection year, longitude, mean July temperature and between-year temperature fluctuations. The proportion of melanic beetles, in line with the thermal melanism hypothesis, increased with increasing latitude and altitude and decreased with increasing climate seasonality. Melanic morph frequencies also declined during the past century, but only at high latitudes and altitudes where recent climate warming was especially strong. The observed patterns suggest that color polymorphism is especially advantageous for populations inhabiting unpredictable environments, presumably due to the different climatic requirements of coexisting color morphs.